PEMBELAJARAN FISIKA FLUIDA STATIS DENGAN MODEL PROJECT BASED LEARNING DISERTAI MIND MAP DI MAN 1 JEMBER - Aprilia Dwi; Trapsilo Prihandono; Subiki Subiki (JURNAL PEMBELAJARAN FISIKA, 2018)
Abstract This study aimed to (1) determined the profile of student learning activitiesthrough project based learning model with mind map in MAN 1 Jember, (2)determined the influence of static fluid learning through project based learning modelwith mind map to student learning outcomes in MAN 1 Jember. The sample of theresearch was the students of class XI MIPA 4 as the control class and the students ofclass XI MIPA 5 as the experimental class. The design of this study used post-test onlycontrol design on static fluid material. Techniques of collecting data usedobservation, tests, and interviews. The data were analyzed descriptively andinferential statistic by using sample t-test (SPSS 24). The result of the research showedthe students' learning activity in physics fluid static learning through project basedlearning model with mind map included in active criterion with percentage 66%. Thestudy of static fluid physics with project based learning model and mind map had asignificant effect on students' cognitive learning achievement. Keywords: Project based learning model, mind map, learning activity,learning achievement.